Tetramethylpyrazine Improves Cognitive Impairment and Modifies the Hippocampal Proteome in Two Mouse Models of Alzheimer's Disease - Huang, Xianfeng; Yang, Jinyao; Huang, Xi; Zhang, Zaijun; Liu, Jianjun; Zou, Liangyu; Yang, Xifei (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases. So far, there is no effective treatment for this condition. Tetramethylpyrazine (TMP) is an alkaloid extracted from traditional Chinese medicine chuanxiong, which is mainly used in the treatment of ischemic stroke some related diseases. In this study, we studied the potential effects of TMP on AD progression by using two AD mouse models. 8-month-old 3xTg-AD mice received TMP treatment (10mg/kg/d) for 1 month, and 4-month-old APP/PS1-AD mice received TMP treatment (10mg/kg/d) for 2 months. The behavioral tests by step-down passive avoidance test (SDA), new object recognition (NOR) and Morris water maze (MWM) showed that TMP significantly improved the learning and memory impairment of two AD transgenic mice. In addition, TMP reduced Aß levels and tau phosphorylation. Venny analysis showed that 116 differentially expressed proteins were commonly changed in 3xTg mice vs WT mice and TMP treated mice vs untreated mice. The same, 130 differentially expressed proteins were commonly changed in APP/PS1 mice vs WT mice and TMP treated mice vs untreated mice. The functions of the common proteins modified by TMP in the two models were mainly related to mitochondrial function, synaptic function, cytoskeleton, GTP binding, ATP binding. Mitochondrial omics analysis revealed 21 and 20 differentially expressed mitochondrial proteins modified by TMP in 3xTg-AD mice and APP/PS1 mice, respectively. These differential proteins were located in mitochondrial inner membrane, mitochondrial outer membrane, mitochondrial gap and mitochondrial matrix, and the function of some proteins is closely related to oxidative phosphorylation of (OXPHOS). Western-blot further validated that TMP changed the expression of OXPHOS complex proteins (sdhb, ndufa10, uqcrfs1, cox5b, atp5a) in the hippocampus of the two AD mice. Taken together, our study demonstrated that TMP improved the cognitive impairment and AD-like pathology, and modified hippocampal proteome in the two AD mice models. The improvement of the behavioral and pathology might be associated with modification of mitochondrial protein profile by TMP. Our study suggested that TMP had the potential for the treatment of AD.